SHOPPING CENTERS IN PERU UNDER NEOLIBERALISM: LIMA LAND EXPANSION AND THE IMPACT IN THE OTHER PERUVIAN CITIES - Andrade, Rita de Cassia Gregorio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
This paper examines commercial spaces in Peruvian cities. The objective is to understand the expansion of shopping centers in the city of Lima and the broader repercussions in Peru, the context of the economic and political transformations of neoliberalism, since the 1990's. The methodological procedures used were literature review, document analysis and cartographic production. Important historical events such as the armed conflict between the Peruvian State and the Maoist Sendero Luminoso group and a concomitant economic crisis disrupted the country in the 1980's. This led to a decline in the operation of shopping centers, which were growing relatively in the 1970's. On the other hand, other commercial spaces emerged during the crisis, most of them linked to the informal sector. As a result of these economic and political factors, it was not until the late 1990's that the process of shopping center expansion resumed within the neoliberal economy promoted by Alberto Fujimori's government. In the context of neoliberal capitalism, modern commercial spaces were established, built and managed by large Peruvian and Chilean economic groups, especially shopping centers. These have expanded and now coexist with other commercial spaces that have not been superseded by urban space, such as supply markets, popular shopping centers and arcades, as well as street markets and high streets. This heterogeneity of spaces and goods offered produced to a diversification in the consumption habits of city dwellers. Finally, we also verified concentration of shopping centers in the city of Lima, in the concentration of shopping centers.
Keywords: Lima; Neoliberalism; Commercial spaces; Shopping center